1977
DOI: 10.1021/bi00631a027
|View full text |Cite
|
Sign up to set email alerts
|

Separation of quantitation of intracellular forms of poliovirus RNA by agarose gel electrophoresis

Abstract: Intracellular poliovirus-specific RNA species can be measured directly by electrophoresis of total cytoplasmic nucleic acids through 1% agarose gels, resulting in the separation of single- and double-stranded forms of poliovirus RNA from each other and from HeLa cell 28S ribosomal RNA. Single-stranded RNA molecules differing by only 15% in length are resolved in this gel system. RNA species can be visualized as fluorescen bands appearing after staining of the gels with ethidium bromide and observation under ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…One picogram of poliovirus RNA corresponds to ϳ250,000 genomes. encapsidated (22). Nonetheless, the two sets of values clearly followed similar trends, as RNA yields and specific virus infectivities declined with increased numbers of replacement codons.…”
Section: Vol 80 2006 Deoptimization Of Synonymous Codon Usage In Pomentioning
confidence: 70%
“…One picogram of poliovirus RNA corresponds to ϳ250,000 genomes. encapsidated (22). Nonetheless, the two sets of values clearly followed similar trends, as RNA yields and specific virus infectivities declined with increased numbers of replacement codons.…”
Section: Vol 80 2006 Deoptimization Of Synonymous Codon Usage In Pomentioning
confidence: 70%
“…Fig. 4(a) shows that, as the infection proceeded, the ratio of Rfto 35S FMDV RNA increased to approximately 1 after 4 h as judged by ethidium bromide staining [Hewlett et al (1977) showed that poliovirus single-stranded RNA and double-stranded RNA gave similar yields of (Fig. 4b).…”
Section: The Replicative Form Of Fmdv Is Less Infectious Than 35s _rnmentioning
confidence: 94%
“…Ribosomal RNA (2.0 A260 units) was incubated with 2 I~g of protein sample in 30 Ixl ofS0 mM-Tris-HC1 pH 7.6 containing 50 mM-KC1 and 5 mM-EDTA at 37 ~ for 15 minutes. After incubation, the RNA was analyzed by electrophoresis on a 1.0% agarose gel (14). The ribonuclease activity on homopolynucleotides was measured in 100 ~tl of 50 mM-Tris-HC1 pH 7.5 containing 50 mM-KC1, 50 ~tg of homopolynucleotide and 10 Ixg of protein as previously described (21).…”
Section: Analytical Proceduresmentioning
confidence: 99%